Narratology and New Historicism in Keong Mas - Retnowati Retnowati; Endang Ernawati (Humaniora, 2017)
The goal of this research was to know how the folktale Keong Mas was narrated based on Vladimir Propp’s Narratology (1968). Then the evidence in the story was compared to the historical evidence happening during the reign of the two dynasties in the Kediri Kingdom in the eleventh century using the theory of New Historicism. This research used a qualitative method which was based on library research. Furthermore, the research is to know that the work of literature is not always independent. It can be traced through the historical evidence in the folktale which becomes their clues. It is to inform the readers that a work of literature is actually the imitation, that is the reflection of the society.